Taxonomy of performance types in Physiotherapy, from technical procedural knowledge to professional performance. - Korell, Mario; Merlo, María Laura (Spanish Journal of Medical Education, 2025)
This paper presents a taxonomy of performance types as a frame of reference for the planning and programming of teaching plans aimed at the development of competencies in Physiotherapy, although it can be applied to other professions. In the literature, there are diverse frameworks based on competency achievement that support the construction of the taxonomy. Additionally, publications related to the topic have been consulted. This is a qualitative development work, through documentary analysis and consultation by survey of kinesiologists who work as clinical practice teachers at the University. Based on the literature review, the need to provide a classification of performances based on procedural knowledge, considering the degrees of integration and levels of complexity, is raised. Five types of performance were identified: those based on technical procedures, strategic procedures, professional tasks, professional activities, and professional being. The article concludes by emphasizing the relevance of the taxonomy for curriculum design, the teaching of kinesiology practices, and the training of health professionals.